Jim Henson's the power of the dark crystal - Spurrier, Simon 1981-; Johnson, Phillip Kennedy (Archaia, 2019)
Years have passed since the Dark Crystal was healed and peace was restored to Thra. Though Jen and Kira have ruled as King and Queen, they have become distracted by power. The planet is sick and those on the surface of Thra are not the only ones affected. A mysterious race of creatures called Firelings live in a realm near the planet's core, hidden from the Gelfling and their kingdom. A young Fireling named Thurman is tasked with stealing a shard of the Crystal to restore power to her world. Along the way she'll befriend the young Gelfling Kensho, conjure the Skeksis and Mystics, and embark on one incredible adventure!
Graphic novelization of the motion picture: The power of the dark crystal, the sequel to Jim Henson's film: The dark crystal
Based on the screenplay by Craig Pearce and Annette Duffy and David Odell
Keywords: Imaginary places -- Comic books, strips, etc; Elves -- Comic books, strips, etc; Mystics -- Comic books, strips, etc; Crystals -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Elfe; Kristall; Young adult fiction; Comics (Graphic works); Comic; Graphic novels; Fantasy comics